International competitive positions of the Baltic States – changes and determinants in the post-accession period - Molendowski, Edward; Petraškevičius, Vladislavas (Journal of Business Economics and Management, 2020)
The article presents the results of an analysis comparing changes in the competitive positions of the Baltic States in comparison with the Visegrad Group countries and the new EU Member States in the post-accession period (2006–2017). This type of study has not been presented in more detail in the available literature. Researchers of international economic competitiveness mostly focussed on the EU-15. The Baltic States mainly have been excluded from such investigations. Therefore, the article may significantly contribute to bridging the gap.The study employs the method of secondary data’s comparative analysis concerning indices and pillars of economic competitiveness described in The Global Competitiveness Reports of the World Economic Forum. An important element of the examination was to identify major determinants of those developments. It focussed on the identification of structural factors shaping the competitive positions of the countries covered. The demonstration which of the factors determine competitiveness and the assessment of long-term changes may serve as the basis for economic policy making.The assumption is that the EU accession had a considerable impact on the development of the competitive position but specific effects varied between countries. The Baltic States differed rather widely regarding the improvement of their competitive positions throughout the post-accession period.